Ekologisk slaktgrisproduktion i Sverige - Karlsson, Johanna (2007)
This literature review describes organic pig production in Sweden, its advantages and disadvantages, but also how its problems can be reduced or solved. Organic pigs have the possibility to a more natural behaviour than conventional pigs. With outdoor pigs comes problems, especially during wintertime, concerning water and feed supply, thermal environment and supervision. Parasites and leakage of plant nutrients are other difficulties that comes with outdoor pigs. All problems and difficulties can be reduced or put right through correct management. Outdoor pigs produce more than meat, they can also contribute with soil preparation.